Reducing patch-like Errors in SAR offset tracking displacements using logarithmic transformation and a weighted NCC algorithm. Issue 4 (3rd April 2023) - Niu, Jingjing; Yang, Zefa; Zhang, Lingling; Lu, Jufeng; Xiang, Yucheng; Tian, Zunhua; Guo, Shanshan
ABSTRACT: Pixel offset tracking (OT) algorithm is a useful tool for measuring large surface displacements by matching amplitudes in master and slave synthetic aperture radar (SAR) images. However, strong backscatters can cause homogeneous errors within a matching window (referred to as patch-like errors) in traditional OT processing, thereby misleading the interpretation of displacement events, especially over a small area. In this letter, we proposed an improved SAR OT algorithm to reduce patch-like errors. In which, a logarithmic transformation was firstly utilized to narrow the SAR amplitude range between strong and weak back scatterers. Strong backscatters causing patch-like errors were then statistically detected with an indicator of median absolute deviation. Finally, those strong backscatters were excluded from SAR OT processing using a weighted normalized cross-correlation scheme, in order to reduce the caused patch-like errors. Two real data tests over the Shuozhou and Yulin coal mining areas, China, suggest that the mean accuracy of the displacements estimated by the presented method improved about 30%, with respect to that estimated by the traditional OT algorithm. The proposed SAR OT algorithm offers a robust option to measure large displacements, especially over a small area, associated with anthropologic or geophysical activities.